Kepastian Hukum Bagi Tenaga Kerja atas Penangguhan Upah dalam Undang-Undang Nomor 13 Tahun 2003 Tentang Ketenagakerjaan - Iswahyudi, Bambang; Effendi, Didik; Imawijaya, R. Afqah Putra; Puspitasari, Diah (El-Qist: Journal of Islamic Economics and Business (JIEB), 2020)
Wage in Indonesia is a concept that refers to several economic systems, but has a characteristic that distinguishes it from other concepts. This is because the economy in Indonesia is based on Pancasila and the 1945 Constitution, so that in terms of wages the role of the government is very dominant or strong in controlling the labor market, creating stability and balance of economic power, and preventing unhealthy competition that can interfere with the interests of workers / laborer. While the wage regulations for workers / laborers in Indonesia still show the existence of regulations that harm the interests of workers / laborers. There is a need for courage from the government to reject all forms of low-wage concepts that are a condition for investors to invest in Indonesia, because by following the conditions of the investors means the government is more pro-investor than for the benefit of workers / laborers whose numbers concern the fate of millions of lower class people. In addition, consideration needs to be given to changing the wage system that bases a certain area (Regency / City Minimum Wage) into a wage system that is based on each industry sector. Keywords: Transparency, Deferral, Wages. Â  Abstrak: Pengupahan di Indonesia merupakan konsep yang mengacu dari beberapa sistem perekonomian, namun memiliki karaktristik yang membedakan dengan konsep-konsep yang lain. Ini disebabkan perekonomian di Indonesia dilandasi oleh Pancasila dan Undang-Undang Dasar 1945, sehingga dalam hal pengupahan peranan pemerintah sangat dominan dalam mengontrol pasar tenaga kerja, menciptakan kestabilan dan keseimbangan kekuatan ekonomi, serta mencegah adanya persaingan yang tidak sehat yang dapat menggangu kepentingan pekerja/buruh. Sedangkan peraturan upah pekerja/buruh di Indonesia masih menunjukkan adanya peraturan yang merugikan kepentingan pekerja/buruh. Perlu adanya keberanian dari pemerintah untuk menolak segala bentuk konsep pengupahan murah yang menjadi syarat investor menanamkan modalnya di Indonesia, karena dengan mengikuti syarat investor tersebut berarti pemerintah lebih memihak kepada investor daripada untuk kepentingan pekerja/buruh yang jumlahnya menyangkut nasib jutaan masyarakat kelas bawah. Selain itu perlu pertimbangan untuk mengubah sistem pengupahan yang mendasarkan suatu kewilayahan tertentu (Upah Minimum Kabupaten/Kota) menjadi sistem pengupahan yang mendasarkan pada masing-masing sektor industri. Kata Kunci: Transparansi, Penangguhan, Upah.